Electroacupuncture Ameliorates Cognitive Impairment and Regulates the Expression of Apoptosis-Related Genes Bcl-2 and Bax in rats with cerebral ischaemia-reperfusion injury. Issue 6 (December 2015) - Liu, Fang; Jiang, Yi-Jing; Zhao, Hong-Jia; Yao, Li-Qun; Chen, Li-Dian
Background: Post-stroke cognitive impairment seriously affects the quality of life and functional rehabilitation of patients with stroke. Objective: To examine the effects of electroacupuncture (EA) at GV20 and GV24 on cognitive impairment and apoptosis including expression of apoptosis-related genes Bcl-2 and Bax in a rat model of cerebral ischaemia-reperfusion (IR) induced by middle cerebral artery occlusion (MCAO). Methods: Thirty-five Sprague-Dawley rats were allocated to a sham operation control group (SC group, n=10) or underwent surgery and MCAO (n=25). Postoperatively the latter group was randomly subdivided into EA or untreated (IR) groups. Cognitive impairment was assessed using the Morris water maze (MWM). Apoptosis was examined by detection of Bcl-2 and Bax expression in the cerebral cortex. Results: The EA group had significantly decreased neurological deficit scores compared to the IR group (p<0.05). In the MWM test, significant differences in escape latency and route were observed between the EA and IR groups (p<0.05). Rats in the EA group performed better in the probe trial than those in the IR group (p<0.05). EA treatment markedly reduced the number of TUNEL-positive cells compared to the IR group (20.13±4.30% vs 38.40±3.38%; p<0.001). Reverse transcription-polymerase chain reaction (RT-PCR) results showed the Bcl-2/Bax ratio was significantly increased in the EA group compared to the IR group (1.61±0.19 vs 0.50±0.05, p<0.01). Conclusions: These findings suggest that EA ameliorates cognitive impairment of rats with IR injury by modulating Bcl-2 and Bax expression.